Well-wrapped reduced graphene oxide nanosheets on Nb3O7(OH) nanostructures as good electron collectors and transporters for efficient photocatalytic degradation of rhodamine B and phenol. Issue 43 (14th April 2016) - Lee, Seunghee; Amaranatha Reddy, D.; Kim, Tae Kyu
Abstract : Nb3 O7 (OH) nanorod-reduced graphene oxide nanocomposites with superior photocatalytic efficiency for degradation of organic dyes have been synthesized and characterized. Abstract : Graphene-based nanocomposites have attracted considerable attention in photocatalytic research owing to their remarkable potential for the photodegradation of environmental pollutants. However, despite the progress made in this field, the development of visible-light-active photocatalysts with high activity and durability remains a challenge. In this work, bunches of Nb3 O7 (OH) nanorods wrapped in reduced graphene oxide (RGO) nanosheets were prepared by using a hydrothermal method. The photocatalytic activity of the as-synthesized Nb3 O7 (OH)-RGO nanocomposites was significantly enhanced compared to that of the pure Nb3 O7 (OH) nanostructures owing to their improved visible-light absorption and separation of photogenerated electron–hole pairs. Photoluminescence studies strongly supported the proposed charge separation and charge transport mechanism. Moreover, the photocatalytic efficiency was strongly dependent on the concentration of RGO in the nanocomposites. The highest photodegradation rate was obtained using the nanocomposite prepared with a graphene loading of 3 mg mL −1, and when the RGO loading exceeded 3 mg mL −1, the photodegradation efficiency decreased. This occurred because excess RGO nanosheets aggregated and hindered the absorption of incident light. We believe that this work provides invaluable information for the design of new efficient visible-light-active reduced graphene oxide-based photocatalysts to be used in water remediation through the oxidative degradation of organic dyes and toxic phenols.